Absidia aguabelensis sp. nov.: A new mucoralean fungi isolated from a semiarid region in Brazil - Leitão, Joana D. A.; Cordeiro, Thalline R. L.; Nguyen, Thuong T. T.; Lee, Hyang B.; Gurgel, Luciana M. S.; Santiago, André L. C. M. De A. (Phytotaxa, 2021)
During a soil survey for Mucorales in a semiarid region of the state of Pernambuco, Brazil, a specimen of Absidia (URM 8213) was isolated. Both morphological and phylogenetic analyses (ITS and LSU rDNA regions) of this specimen showed that it is a new species. The new species differs from other species in the genus in its ability to concomitantly produce isolated or whorled sporangiophores of up to 8 with fig-shaped and hemispherical columellae, as well as globose, subglobose, and cylindrical sporangiospores. Thus, in this study, we propose a new species of Absidia.